MRI-detectable polymeric micelles incorporating platinum anticancer drugs enhance survival in an advanced hepatocellular carcinoma model - Vinh NQ (Dove Medical Press, 2015)
Nguyen Quoc Vinh,1 Shigeyuki Naka,1 Horacio Cabral,2 Hiroyuki Murayama,1 Sachiko Kaida,1 Kazunori Kataoka,2 Shigehiro Morikawa,3 Tohru Tani4 1Department of Surgery, Shiga University of Medical Science, Shiga, Japan; 2Department of Bioengineering, Graduate School of Engineering, The University of Tokyo, Tokyo, Japan; 3Department of Nursing, Shiga University of Medical Science, Shiga, Japan; 4Biomedical Innovation Center, Shiga University of Medical Science, Shiga, Japan Abstract: Hepatocellular carcinoma (HCC) is one of the most intractable and lethal cancers; most cases are diagnosed at advanced stages with underlying liver dysfunction and are frequently resistant to conventional chemotherapy and radiotherapy. The development of tumor-targeting systems may improve treatment outcomes. Nanomedicine platforms are of particular interest for enhancing chemotherapeutic efficiency, and they include polymeric micelles, which enable targeting of multiple drugs to solid tumors, including imaging and therapeutic agents. This allows concurrent diagnosis, targeting strategy validation, and efficacy assessment. We used polymeric micelles containing the T1-weighted magnetic resonance imaging contrast agent gadolinium-diethylenetriaminpentaacetic acid (Gd-DTPA) and the parent complex of the anticancer drug oxaliplatin [(1,2-diaminocyclohexane)platinum(II) (DACHPt)] for simultaneous imaging and therapy in an orthotopic rat model of HCC. The Gd-DTPA/DACHPt-loaded micelles were injected into the hepatic artery, and magnetic resonance imaging performance and antitumor activity against HCC, as well as adverse drug reactions were assessed. After a single administration, the micelles achieved strong and specific tumor contrast enhancement, induced high levels of tumor apoptosis, and significantly suppressed tumor size and growth. Moreover, the micelles did not induce severe adverse reactions and significantly improved survival outcomes in comparison to oxaliplatin or saline controls. Our results suggest that Gd-DTPA/DACHPt-loaded micelles are a promising approach for effective diagnosis and treatment of advanced HCC. Keywords: Gd-DTPA/DACHPt-loaded micelles, polymeric micelles, drug delivery, hepatocellular carcinoma